2023
DOI: 10.1200/jco.23.00434
|View full text |Cite
|
Sign up to set email alerts
|

Adagrasib in Advanced Solid Tumors Harboring a KRASG12C Mutation

Abstract: PURPOSE Adagrasib, a KRASG12C inhibitor, has demonstrated clinical activity in patients with KRASG12C-mutated non-small cell lung cancer (NSCLC) and colorectal cancer (CRC). KRASG12C mutations occur rarely in other solid tumor types. We report evaluation of the clinical activity and safety of adagrasib in patients with other solid tumors harboring a KRASG12C mutation. METHODS In this phase II cohort of the KRYSTAL-1 study (NCT03785249; https://www.clinicaltrials.gov/ct2/show/NCT03785249 ; phase Ib cohort), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Additionally, the limited reporting of KRAS testing in cancer types other than the two predominant ones, colorectal and lung cancer, which are among the most prevalent and lethal worldwide, may be attributed to the fact that targetability of KRAS mutations in other cancer types than lung and colorectal cancers was only recently recognized. 13,[23][24][25][26][27] Such testing has the potential to increase access to innovative drugs in the experimental setting, accelerate drug development, and contribute to our understanding of the impact of KRAS mutations in these less common cancer types. Despite overall increased testing, substantial regional variations persist due to differences in testing strategies and reporting practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the limited reporting of KRAS testing in cancer types other than the two predominant ones, colorectal and lung cancer, which are among the most prevalent and lethal worldwide, may be attributed to the fact that targetability of KRAS mutations in other cancer types than lung and colorectal cancers was only recently recognized. 13,[23][24][25][26][27] Such testing has the potential to increase access to innovative drugs in the experimental setting, accelerate drug development, and contribute to our understanding of the impact of KRAS mutations in these less common cancer types. Despite overall increased testing, substantial regional variations persist due to differences in testing strategies and reporting practices.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this approach, recent findings from the phase I trials with adagrasib and sotorasib in patients with advanced KRAS G12C solid tumors demonstrated the clinical efficacy of KRAS G12C targeted therapy in multiple tumor types, and the FDA recently approved dabrafenib plus trametinib for all BRAF V600E mutated solid tumors. [13][14][15] Advancements in targeted therapies is closely linked to technological progress in sequencing, notably the adoption of nextgeneration sequencing (NGS) using comprehensive panels for detecting a large number of genetic variations in a single analysis. 16 NGS has now become a standard diagnostic tool, often replacing quantitative polymerase chain reaction (qPCR) testing.…”
Section: Introductionmentioning
confidence: 99%
“…13 Although much rarer, occurring in 1%-2% of pancreas cancers, the KRAS G12C mutation can also be targeted with small-molecule inhibitors, showing promising antitumor activity in early clinical trials (NCT03600883 and NCT03785249). [14][15][16] In the case of the Code-BreaK 100 trial, the KRAS G12c inhibitor sotorasib had an ORR of 21% and median progression-free survival (mPFS) of 4 months (95% CI, 2.8-5.6). 14 In the KRYSTAL-1 study, a similar drug called adagrasib demonstrated an objective response rate (ORR) of 32.2% in pancreatic cancer with a mPFS of 7.4 months (95% CI, 5.3-8.6).…”
Section: Clinical Advancesmentioning
confidence: 99%
“…14 In the KRYSTAL-1 study, a similar drug called adagrasib demonstrated an objective response rate (ORR) of 32.2% in pancreatic cancer with a mPFS of 7.4 months (95% CI, 5.3-8.6). 16 Indeed, as in other malignancies, personalization of treatment has emerged as a promising approach for pancreatic cancer. There (not reached vs. 13.4 months, p = .003).…”
Section: Clinical Advancesmentioning
confidence: 99%
“…Though RAS proteins were long regarded as "undruggable" targets, recent advances have led to the development and approval of agents that target one specific RAS variant, KRAS G12C 4,5 . This strategy has shown promising efficacy in KRAS G12C mutant tumors, including the small fraction (~1%) of PDAC cases harboring this allele 6,7 .…”
mentioning
confidence: 99%